The effects of the Corona pandemic on the current and future situation of organizing and holding events and occasions: a field study on the General Entertainment Authority in Kingdom of Saudi Arabia - Iraqi, Rayan AbdulAziz; Al-Abdali, Shaheen Sulaiman; Alansari, Mansour Talal Abid (Arab Journal for Sciences and Research Publishing, 2023)
The current research study aims to shed light on the effects resulting from the Corona pandemic and the extent to which the current and future situation of organizing and holding events and occasions in the General Entertainment Authority in the Kingdom of Saudi Arabia is affected by it. To achieve the goal of the study, the researchers adopted the descriptive analytical approach in preparing the study, with the use of the questionnaire as a tool for collecting data from the study sample members. Where this study was applied to a sample of employees working in the General Entertainment Authority, and the sample size are 149 employees. The study reached a set of results, most notably: the presence of a large degree of approval from the study sample members about the (economic, social, psychological, and health) effects of the Corona pandemic within the General Entertainment Authority. The results also indicated that there is a direct statistically significant impact of the (economic, social, psychological, and health) effects resulting from the Corona pandemic on the mechanism of organizing events and occasions for the General Entertainment. In light of these results, the researchers recommended a number of recommendations, most notably: Strengthening the communication channels of the Ministry of Human Resources and Social Development and the competent bodies to find alternative job opportunities for workers in the General Entertainment Authority during the Riyadh season who were laid off as a result of the economic effects of the pandemic. Additionally, Organizing online events and live broadcasting of “virtual events” events.